Nutrição, proteção e qualidade da bebida do café sob pulverizações de silicato de potássio líquido solúvel - Figueiredo, Felipe Campos (2007)
Three experiments were conducted so that the first one had as objective to evaluate the effects of the foliar spraying of sources and doses of soluble liquid potassium silicate (Meta e Sili-K) on the coffee leaf rust, compounds of defense, production and quality and the coffee beverage. The second experiment aimed to evaluate the association of the better source of soluble liquid silicon (Sili-K) with fungicide in the control of diseases, and the third experiment evaluated the absorption of micronutrients when they are associated with Sili-K in the spraying solution and comparing it with other solutions. It was possible to conclude that the foliar spraying with soluble liquid silicon had influenced the ratio of different stages of the maturation of the fruits that affected the income and production of coffee. The Meta was significantly inferior to Sili-K when reducing high sieve in the high production harvest while the Sili-K raised the ratio of these sieve in the low production harvest; the best effects were observed between the doses of 1710 and 5000 mg L-1. In the same rate of dose and independent of the source used, there was improvement of the grades of "acidity" and "balance" of the beverage in the low harvest, and of the "body" of the beverage independent of the harvest. Contents of Si and K in leaf were indirectly related with the quality of the beverage in the low production harvest and in the relaxation of the biennial of the coffee production. The sources and doses of potassium silicate did not raise from the foliar contents of Si and K in spite of their contents to be positively related to the production the next harvest. The Sili-K has showed itself superior to Meta in the reduction of the incidence of the coffee rust, however, there was reduction of disease severity independent from the source. The images of electronic microscopy made evident a larger re-covering of the foliar surfaces with increase of the Si doses. The increase of Si and K contents and the reduction of the contents of total phenols are connected with the rise of productivity in the following harvest and can be further considered indexes of productive potential of coffee. In the association of 2 L ha-1 of soluble liquid silicon (Sili-K) with half of the prescribed dose of fungicide (750ml ha-1 of epoxiconazole + pyraclostrobin) in the solution, rust and brown-eye-spot were controlled similar to the prescribed dose of fungicide (1,5 L ha-1 and 1 L ha-1 in the 1st and 2nd application respectively).The occurrence of foliar diseases was not related to the foliar contents of K or Si. The mixture of micronutrients with soluble liquid silicon in solution had increased the absorption of Cu, 30 days after the application and it was similar to the Viçosa solution concerning to the supplying of B, Zn and Mn.